The Orphic voice poetry and natural history - Sewell, Elizabeth 1919-2001 (New York Review Books, 2022)
"The Orphic Voice is a book about the relationship between poetry and our place in and knowledge of the natural world written by one of the most original, distinguished, and visionary literary thinkers of the late twentieth century. Taking its bearings from the Greek myth of Orpheus, whose singing had the power to move the rocks and trees and to quiet the animals, The Orphic Voice is an exercise in what Sewell calls mythic thinking. Myth is not, she argues, mere fable; it is instead a way of configuring our fundamental bonds to the living universe, and mythic thinking represents an ancient and vital form of reflection, uniting great poets like Shakespeare and Wordsworth and Rilke to remarkable thinkers and scientists as Francis Bacon, Giambattista Vico, and Michael Polanyi. The members of this Orphic company share a common perception that "discovery, in science and poetry, is a mythological situation in which the mind unites with a figure of its own devising as a means toward understanding the world." Sewell's visionary book, first published in 1960, offers transformative readings of A Midsummer Night's Dream, The Prelude, and Rilke's Songs of Orpheus, among other masterpieces, while deepening our understanding not only of literature but of our biological and sexual being and bond to nature as a whole"--